STRATEGI PEMASARAN TEH HITAM MERK “ALAM DEMPO” PADA CV. KARYA SEJAHTERA PAGAR ALAM - Khadijah, Tiffany Siti; Irnad, Irnad; Utama, Satria Putra (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2016)
This study aims to determine the main criterion used in marketing strategies and the strategies marketing appropriate and effective in marketing black tea brands “Alam Dempo’’ on CV. Karya Sejahtera. The primary data was obtained from interviews and secondary data obtained from the data from of the company, regulations, and others data from the related agencies. The data was analyzed by using the AHP (Analytical Hierarchy Process) with Application Expert Choice 11. The results of research show that the criteria becomes main priority election marketing strategies black tea was is competitor with weight 0.385. This occurred due to large number of business contractors packaging black tea other products. To alternate top priority marketing strategies was chosen by method AHP is promotion strategy with weight 0,360.